The winds and the waves that carved out today’s coastal landscape of Sines (Portugal) - Fernandes, Jacinta (2021)
The Atlantic maritime winds and waves, as natural forces, shaped the physiography of Sines, a peculiar rocky cliff cape at the western Portuguese coast, as well as cultural processes have shaped its spatial arrangement since ancient times. Despite its small size, Sines port has always been an important maritime trade corner. In the 1970s, winds and waves of modernity reached the Sines coast with an imposing industrial-port complex. We present the history of Sines cape focusing on its landscape dynamics. The patch-corridor-matrix model allowed us to describe the mosaic transformation of such a unique landscape. Spatial information was gathered mostly from historical maps processed with digital tools. A time series of thematic maps (landscape mosaic pattern) was obtained, covering more than 120 years. Current results emphasize that this landscape underwent relevant transformations related to human activities since former times, although disturbance and fragmentation of the landscape were strongly intensified after the arrival of the post-modern wave of the industrial culture. The present study provides a contribution to the history of the Portuguese and Mediterranean coastal landscapes; and results could be used to support decision making in sustainable management of this territory.